International relations theory and South Asia security, political economy, domestic politics, identities, and images. Vol. 2 - Sridharan, Eswaran (New Delhi : Oxford University Press, 2011)
This volume explores security, political economy, and domestic politics in South Asia. Focusing on neglected inter-relationships between distinct issues, it presents a complete picture of international relations in the region.
Includes bibliographical references.
Description based on print version record.
Keywords: National security -- South Asia; South Asia -- Foreign relations -- 21st century; South Asia -- Politics and government -- 21st century